Conservation agriculture with trees: a training manual - Mercado, A.R.; Linayao, J.; Piñon, C. (World Agroforestry Centre, 2020)
Through text and technical illustrations, this manual discussed the following topics: 1.soil health and its importance, 2.conservation farming and its principles, 3.conservation agriculture with trees and its related principles, 4.equipment used in conservation farming